Membangun Masa Depan Aman: Strategi Efektif dalam Perlindungan Anak - Choirul Maromi; Miftakhul Jannah; Yes Matheos Lasarus Malaikosa (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This research uses the Systematic Literature Review (SLR) method to explore the main challenges in child protection as well as effective strategies for overcoming these challenges. This research was carried out through a series of systematic stages, starting from formulating research questions, literature search, literature selection, data extraction, data analysis and synthesis, to presentation of results. The main challenges in child protection include violence against children and exploitation of children in various forms. Effective strategies include cross-sector collaborative approaches, community education, and strengthening local child protection systems. Implementation of this strategy requires adaptation to different local contexts, as illustrated in case studies in Indonesia. The SLR method was used to ensure a comprehensive and reliable analysis by minimizing research bias. Validity and reliability were strengthened through data triangulation and independent analysis by two researchers. It is hoped that the results of this research can provide a strong foundation for the development of child protection policies and programs, not only in Indonesia but also in other countries that face similar challenges. This research makes an important contribution to the understanding of effective child protection strategies, as well as offering practical recommendations for the implementation of child protection policies in various contexts.